Relationship Quality in Early Adult Individuals That Are in Long-Distance Relationships - Danny Sanjaya Arfensia; Putu Diana Wulandari; Respianto Respianto; Satria Kamal Agassi; Riris Ristiana; Putu Vidyastitha Wiguna; Wiwin Hendriani; Ilham Nur Alfian (Psychosophia: Journal of Psychology, Religion, and Humanity, 2021)
Technological advances make communication easier for couples who have long-distance relationships. The quality of the relationship between a couple who being apart and being together is not necessarily the same, especially when it comes to intimacy. This study aims to determine the quality of relationships in early adults who undergo long-distance relationships. The qualitative research method was chosen with a case study approach that focuses on how the individual interacts in long-distance relationships. Data collection techniques in this study using interviews. The subjects of this study were 2 early adult couples who had a long-distance relationship between Surabaya and outside Surabaya and the couple had been in a relationship for at least 1 year. The data analysis technique used in this research is thematic analysis technique theory driven. The results indicate that respondent 1 shows relationship satisfaction despite feeling uncomfortable with the relationship being undertake. Respondent 2 showed relationship satisfaction but not appreciate his partner's achievements. From these results can be concluded that the quality of the relationship of each partner who has a long-distance relationship is different.